Action research and educational technology: Cultivating disruptive learning - Waghid, F. (South African Journal of Higher Education, 2020)
Nowadays, teaching and learning in South African university classrooms seem to be most prominently spoken of in relation to transformation. In this article, I argue as to why action research offers a pedagogical approach to enhance transformative (disruptive) learning in university classrooms. Firstly, I give an account of action research and how it came to manifest in university education. Secondly, I show as to how educational technology can be used to enhance disruption within pedagogical encounters. And, thirdly, in relation to democratic educational theory I show as to how, using Jacques Ranciere’s ideas of disruption and coming to speech can enhance learning through action research.